Development of Nectin4/FAP-targeted CAR-T cells secreting IL-7, CCL19, and IL-12 for malignant solid tumors - Li, Fanfan; Zhao, Shuping; Wei, Cheng; Hu, Yaodi; Xu, Tianlong; Xin, Xueyi; Zhu, Tingwei; Shang, Liting; Ke, Shanwen; Zhou, Jiang; Xu, Xiaojun; Gao, Yue; et al. (Frontiers in Immunology, 2022)
Background Chimeric antigen receptor T (CAR-T) cell therapy has made significant advances for hematological malignancies but encounters obstacles in the treatment of solid tumors mainly due to tumor immunosuppressive microenvironment. Methods Immunohistochemistry analysis was performed to examine the cellular expression of nectin cell adhesion molecule-4 (Nectin4) and fibroblast activation protein (FAP) in a variety of malignant solid tumors. Then, we engineered the fourth-generation Nectin4-targeted CAR-T (Nectin4-7.19 CAR-T) and FAP-targeted CAR-T (FAP-12 CAR-T) cells to evaluate their safety and efficacy in vitro and in vivo. Results In our study, we firstly demonstrated the aberrant overexpression of Nectin4 on both primary and metastatic solid tumors and FAP on cancer-associated fibroblasts. Then, we found that our fourth-generation Nectin4-7.19 CAR-T cells expressed IL-7 and CCL19 efficiently and exhibited superior proliferation, migration, and cytotoxicity compared to the second-generation Nectin4 CAR-T cells, while FAP-12 CAR-T cells exerted their ability of targeting both murine and human FAP effectively in vitro. In a fully immune-competent mouse model of metastatic colorectal cancer, lymphodepletion pretreated mice achieved complete remission with human Nectin4-targeted murine CAR-T (Nectin4 mCAR-T) cells. In the NSG mouse model of lung metastases, Nectin4-7.19 CAR-T cells eradicated metastatic tumors and prolonged survival in combination with FAP-12 CAR-T cells. Conclusions These findings showed that Nectin4-7.19 CAR-T cells had potential therapeutic efficacy and exerted a synergistic role with FAP-12 CAR-T cells, further demonstrating that Nectin4 and FAP were able to serve as promising targets for safe and effective CAR-T therapy of malignant solid tumors.